An innovative approach to enhance sustainability of a district cooling system by adjusting cold thermal storage and chiller operation. (1st January 2021) - Anderson, Austin; Rezaie, Behnaz; Rosen, Marc A.
Abstract: Enhancing sustainability, performance, and saving costs, are important goals for the district heating and cooling industry. There are many options for the upgrading and alteration of the equipment which demand a large initial investment. Usually, the initial cost is a barrier to implementing the plan. In this study, sustainability, performance, and cost savings are improved without any equipment change. Exergy assessment along with TRNSYS modeling and simulation are the tools applied in this study. The focus is on the operation time of the equipment. By adjusting the operation time of the equipment with the highest exergy destruction, in the district cooling in the University of Idaho, Moscow campus in the United States of America (USA) all three goals without any equipment change has been achieved. The operation hours of cold thermal energy storage (TES), cooling towers, and chillers are altered by removing the low efficiency operation time. As results electricity consumption is reduced to 38%, which is beneficial in terms of sustainability, as it eliminates 428, 800 kg CO2 emissions in electricity generation and provides an annual cost saving of $140, 000. Ultimately, modification of the equipment operation in district cooling is a key to improvement of sustainability and cost saving. Highlights: Operation schedule alteration improved sustainability for 428 ton of CO2 in the UI district cooling systems. The charging and discharging time of the cold TES in the UI district cooling has significant role in energy saving. Cooling towers by dissipating heat have the highest exergy lost in cooling systems. Electricity use reduced 38% by changing the operations schedules in the UI cooling system without changing any equipment. Cost saving in the UI district cooling has been $140, 000 annually by changing the operation schedule.